2017
DOI: 10.1080/10495398.2017.1366340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism and Bottleneck Analysis of Balkhi, Hashtnagri, and Michni Sheep Populations Using Microsatellite Markers

Abstract: Pakistan is rich in sheep genetic resources. Balkhi, Hashtnagri, and Michni are neighboring sheep populations found in Khyber Pakhtunkhwa province of Pakistan. In this study, we analyzed the genetic structures and bottleneck incidents within these sheep populations using 31 microsatellite DNA markers. Total numbers of 116, 100, and 95 alleles, with average numbers of 3.20, 3.26, and 3.74 alleles per locus were observed, respectively, in Balkhi, Hashtnagri, and Michni population. Mean observed heterozygosity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…While, in El-Dakhla sheep population ranged from 0.039 (for BM1314 in allele 133 and 172) to 0.385 (for BM8125 in allele 78), Also, in El-Farafra sheep population ranged from 0.024 (for BM757 in allele 210) to 0.175 (for OarHH47 in allele 49) as shown in table 2. In Hashtnagri sheep the frequency of null alleles ranged from 0.017 (BM1329) to.959 OarCP38 and in Michni population null alleles were found at highest frequency at six loci ranged from 0.001 (BM8125) to 0.830 (ILSTS5) by (Ibrahim et al, 2010). El-Sayed et al, (2017) reported that the highest allele frequency for overall loci was 1.00 for allele 244 at locus CSRD247 in the case of Damascus goat breed and the lowest one was 0.0500 associated with Farafra goat population at locus TCRVB6 (for alleles 210 and 240).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…While, in El-Dakhla sheep population ranged from 0.039 (for BM1314 in allele 133 and 172) to 0.385 (for BM8125 in allele 78), Also, in El-Farafra sheep population ranged from 0.024 (for BM757 in allele 210) to 0.175 (for OarHH47 in allele 49) as shown in table 2. In Hashtnagri sheep the frequency of null alleles ranged from 0.017 (BM1329) to.959 OarCP38 and in Michni population null alleles were found at highest frequency at six loci ranged from 0.001 (BM8125) to 0.830 (ILSTS5) by (Ibrahim et al, 2010). El-Sayed et al, (2017) reported that the highest allele frequency for overall loci was 1.00 for allele 244 at locus CSRD247 in the case of Damascus goat breed and the lowest one was 0.0500 associated with Farafra goat population at locus TCRVB6 (for alleles 210 and 240).…”
Section: Resultsmentioning
confidence: 96%
“…While, the allele numbers were lower than those reported by ozerov et al, (2008) out line that in all, 233 alleles were found across the 20 microsatellite loci and the number of alleles at the locus varied from 6 (OarCP34) to 17 (BM4621, CSSM31, and OarFCB304) with an average value of 12 in sheep of the four Kazakh breeds. Ibrahim et al, (2010) reported that number of 119 alleles across 31 SSR loci in three sheep populations was identified from three breeds Balkhi, Hashtnagri and Michni.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations